Сучасна біотехнологія в оптимізації утилізації рослинних відходів - Zaimenko, Nataliia; Ivanytska, Bohdana; Pavliuchenko, Nataliia; Slyusarenko, Olexandr; Tian, Lijuan; Miao, Tianlin; Liu, Dejiang; Pyzyk, Myron; Slaski, Jan (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
The study aimed to develop a modern, cheap, and environmentally safe technology for the disposal of plant waste, with the participation of the most active microorganisms-destructors.The microorganisms’ ability to help transform plant waste into viable, fertile soil was extensively studied. We selected strains of micromycetes Penicillium roseopurpureum, Trichoderma hamatum, T. koningii, Alternaria alternata, and bacteria of the genus Cytophaga, which are characterized by high growth rate and the absence of phytotoxicity. To accelerate microorganism development, we used silicon-containing mineral analcime, which contained immobilized spores of micromycetes and bacterial cells’ suspensions. Modified analcime was added to the waste in a ratio of 10 : 1. The plant remains prepared in this method were analyzed under conditions of both model and vegetation experiments.An evidence for the expediency of using the silicon-containing mineral analcime as a starting substrate for immobilization of spores and suspension of bacterial cells in the culture fluid was provided. The microorganisms involved in the experiment showed a positive result in transforming plant waste during the 30-day observation period. The highest destructive activity against apple and grape waste is characteristic for the T. hamatum strain, for beet waste – P. roseopurpureum. The species-specificity of these destructive microorganisms on plant growth processes was proved. The maximum growth of corn sprouts in apple waste was detected by inoculation with T. koningii spores, grape waste – T. hamatum, and beet waste – a mixture of micromycetes with a Cytophaga sp. suspension. The optimal duration of plant waste transformation using analcime, inoculated with microorganisms, is 20–30 days. In the indoor farming conditions, the standard for utilizing the modified vegetable waste placement was 10 % of the total volume of a substrate during the preparation of soil mixes.The environmental safety of plant waste after their destruction was confirmed. The presence of a silicon-containing mineral in the mixture leads to increased growth and plant development, optimization of the agrophysical, agrochemical, and biological parameters of the soil, reducing soil fatigue, and increasing fertility.